Sensory Effect Extraction for 360° Media Content - Abreu, Raphael; Santos, Joel A. F. dos; Muchaluat-Saade, Débora C. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2021)
The presentation of sensory effects in sync with 360° content has the potential to increase user immersion. However, the authoring process for such effects is laborious and slow. It requires the author to specify in time and space the presentation characteristics of effects. This paper contributes to address this need with a generic architecture for inferring the presentation characteristics of sensory effects in 360° content. The proposed architecture decouples and eases the adaptation of multimedia content analysis techniques for recognizing sensory effects. We highlight the original contribution of this work of presenting the automatic recognition of sensory effects location in 360° content.